2015
DOI: 10.5194/acpd-15-3285-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impacts of atmospheric circulations on aerosol distributions in autumn over eastern China: observational evidences

Abstract: Abstract. Regional heavy pollution events in East China (110–122° E, 28–40° N) are the main environmental problems recently because of the high urbanization and rapid economic development connected with too much emissions of pollutants. However, appropriate weather condition is another factor which cannot be ignored for these events. In this study, the relationship between regional pollution status and larger scale atmospheric circulations over East China in October is investigated using ten-year (2001–2010) M… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In addition, some specific synoptic patterns might also cause noticeable changes in both UHII and PM 2.5 . Synoptic patterns can affect air quality episodes which are already expressed through the meteorological variables (e.g., temperature, wind speed, rainfall, and cloud cover), and thus, these variables can represent a certain synoptic situation over a given region (Kassomenos et al, ; Luo et al, ; Miao et al, , ; Ning et al, , ; Shahgedanova et al, ; Wang, Liu, et al, ; Yang Yim et al, ; Zheng et al, ). The possibly different associations between the UHII and PM 2.5 under different synoptic patterns will be the focus of a future study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some specific synoptic patterns might also cause noticeable changes in both UHII and PM 2.5 . Synoptic patterns can affect air quality episodes which are already expressed through the meteorological variables (e.g., temperature, wind speed, rainfall, and cloud cover), and thus, these variables can represent a certain synoptic situation over a given region (Kassomenos et al, ; Luo et al, ; Miao et al, , ; Ning et al, , ; Shahgedanova et al, ; Wang, Liu, et al, ; Yang Yim et al, ; Zheng et al, ). The possibly different associations between the UHII and PM 2.5 under different synoptic patterns will be the focus of a future study.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies (Borge et al, 2007;Guo et al, 2017;Osborne et al, 2019;Zheng et al, 2015), backward trajectories for identified particulate matter pollution episodes were computed using Numerical Atmospheric-dispersion Modelling Environment to identify the impacts of transboundary air pollution and local PM pollution in Hong Kong (Jones et al, 2007). Briefly, the Numerical Atmospheric-dispersion Modelling Environment model is a Lagrangian transport model that is driven by model forecast winds or reanalysis data with variable spatial resolutions (Walters et al, 2017).…”
Section: 1029/2019jd031140mentioning
confidence: 99%
“…The negative impact of relative humidity strengthened gradually from north to south, corresponding to the more humid climate. In addition to the clean air mass from the sea, strong southeastward cold-air advection prevailed in autumn, maintaining wind speed as a dominant factor mitigating air pollution in eastern and southern coastal regions [44].…”
Section: Spatial Clustering Analyses: Autumnmentioning
confidence: 99%